Yes-associated protein reduces neuroinflammation through upregulation of Sirt3 and inhibition of JNK signaling pathway. (2nd November 2019) - Yang, Yang; Gong, Zhongying; Wang, Zhiyun
Abstract: Objective: Neuroinflammation is linked to a series of neurodegenerative diseases through the unknown mechanisms. Aim: The aim of this study was to investigate the role of Yes-associated protein (Yap) in the regulation of neuroinflammation. Methods: BV-2 neuroglia cells were treated with TNFα in vitro . Then, western blots, qPCR, immunofluorescence, and ELISA were used to verify the influence of Yap in BV-2 cells neuroinflammation response. Results: After exposure to TNFα, viability of BV-2 cells decreased whereas apoptosis index was increased. Of note, Yap expression in BV-2 cells was significantly reduced, when compared to the normal cells. Interestingly, adenovirus-induced Yap overexpression was capable to reverse cell viability and thus reduce apoptotic index in TNFα-treated BV-2 cells. Molecular investigation demonstrated that Yap overexpression was linked to Sirt3 upregulation. Increased Sirt3 reduced endoplasmic reticulum (ER) stress, attenuated mitochondrial damage, and blocked JNK pro-apoptotic pathway. Interestingly, loss of Sirt3 abolished the protective effects induced by Yap overexpression in TNFα-treated BV-2 cells. Conclusions: Altogether, our results demonstrated that neuroinflammation could be caused by Yap downregulation, possible driven through Sirt3 inhibition and JNK activation. However, overexpression of Yap could protect BV-2 cells against TNFα-mediated apoptosis through modulating Sirt3-JNK signaling pathways.